Inobservancia de la ética profesional en los operadores de justicia al emitir sentencia. - González Ortega, Josselyn Fernanda (2018)
The professional ethics, is aimed at determining the behavior of the person in the field of labor, subject always to the principles, values and morality that is, to act correctly within society; justice operators, in the different areas of law in which they operate, whether criminal, civil, constitutional, labor, among others, to issue a judgment, are based on what the legal norms in force, evidence provided by the parties to the proceedings; the General Organic Code of Processes, in its article 164, second paragraph, states that the judge must apply the rules of sound criticism in the evaluation of the evidence, rules that allow the correct logical reasoning and take the maximum experience that has within the matter to rationally motivate the sentence; the judge is called to watch over and guarantee the due fulfillment of rights, in favor of justice, the sound criticism in every legal system is nothing else than the guide or model for the critical analysis of the probative material practiced in the process; within the evaluation of the evidence, necessarily fits the facts, with the current regulations and the sound criticism of the judge, thus forming an enforcement mechanism, allowing the justice operator to reach the procedural truth of the manifested, by the procedural parties, and issue a sentence, based on a legally proven fact, that is, true, achieving the correct application of justice; the above stated as valid, the Ecuadorian legislation, as is the Constitution of the Republic of Ecuador, in article 76, paragraph 7, subsection (l), provides that operators will motivate its resolutions, with the purpose of preventing the violation of rights by specifying the relevant rules and regulations, it is there to suit the fact to the right, is the home of the judicial process, and by reason of non-compliance there is a penalty, for those staff members who do not comply with such provisions; in this particular case it can be shown that the justice operator did not make the pertinent valuation of the evidence presented in the extraordinary prescription of acquisitive domain, did not respect the rules of logic, much less acted ethically, all justice operators are guarantors of the legal security that people have as users of the judicial function, are responsible for providing justice by the basis of the decision taken, giving a reasonable explanation of the reasons that support it, mentioning the elements of conviction that took into consideration and what was the probative value that is granted to each of them; the ethics plays a primary role in the legal field because it has a close relationship with the right, when searching for the social good or common ethical commitment contributes to the excellence in the competence and professional performance, as well as a balance between the fundamental values such as the middle of the moral condition of each individual, which is determined according to the needs of each society may be in any space of time; the construction of professional codes in the different fields of work relating to the legality of the acts and conduct, allowing to act with responsibility and conscience taking as part of their objectives the implementation of principles and values in the field basically both social and professional.